Graphite-compatible low-concentration high-temperature flame-retardant lithium ion battery electrolyte and preparation method and application thereof

By using lithium-ion battery electrolytes and lithium salts with high thermal decomposition temperatures to form a lithium fluoride-rich SEI film, the problem of stable operation of lithium-ion batteries is solved, and the high temperature stability and safety are improved.

CN119852524APending Publication Date: 2025-04-18NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410390729.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-04-02
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The existing lithium-ion battery electrolyte has safety hazards at high temperatures, the working temperature range is narrow, and the interface desolvation is slow, resulting in the battery being unable to operate stably in a high temperature environment.

Method used

A low-concentration, high-temperature flame-retardant lithium-ion battery electrolyte is used that is compatible with graphite. The raw materials include the combination of carbonate compounds and fluorocarbonate compounds, as well as lithium salts with high thermal decomposition temperatures, such as difluorooxalic acid compounds, to form a protective SEI film rich in lithium fluoride through these components to inhibit interfacial side reactions.

Benefits of technology

The lithium-ion battery is realized to operate stably at a high temperature of 60℃, which improves the high temperature stability and safety of the battery, avoids the problems of electrolyte decomposition and intensified side reactions, and improves the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852524A_ABST
    Figure CN119852524A_ABST
Patent Text Reader

Abstract

The invention relates to a low-concentration high-temperature flame-retardant lithium ion battery electrolyte compatible with graphite as well as a preparation method and application thereof, and belongs to the technical field of electrolytes. The invention discloses a low-concentration high-temperature flame-retardant lithium ion battery electrolyte compatible with graphite. Raw materials of the electrolyte comprise an organic solvent and a lithium salt, the organic solvent comprises a carbonic ester compound and a fluoro carbonic ester compound in a volume ratio of 1: (0.1-10); the thermal decomposition temperature of the lithium salt is greater than or equal to 250 DEG C. The negative ions of the lithium salt can enhance the interaction between lithium ions and other negative ions and enhance the complexation; the synergistic effect of the fluorocarbonate compound solvent and the lithium salt can improve the solvation structure of the electrolyte to a great extent, and the electrolyte can be better compatible with graphite; a lithium ion battery based on the low-concentration high-temperature flame-retardant lithium ion battery electrolyte compatible with graphite can stably operate at the high temperature of 60 DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrolytes, and relates to a low-concentration, high-temperature, flame-retardant lithium-ion battery electrolyte that is compatible with graphite, and a preparation method and application thereof. Background Art

[0002] Advanced electrolytes are an indispensable part of the next generation of lithium-ion batteries. However, the strong solvation between lithium ions and polar solvents will lead to slow desolvation of the interface and the phenomenon of solvent co-embedded graphite. The most widely used electrolyte system currently uses carbonate solvents with high volatility, low ignition point and high melting point and LiPF6 with low thermal decomposition temperature as lithium salts. Its operating temperature is limited to -20 to 40°C, the working range is narrow, and there are safety hazards such as fire and explosion, which severely restricts the development of lithium-ion batteries in high-temperature surveys, military equipment and other fields. As a key component of lithium-ion batteries, electrolytes are the most flammable and temperature-restricted part of the battery structure. Therefore, it is urgent to develop electrolytes with good safety and stable circulation over a wide temperature range. Summary of the invention

[0003] The purpose of the present invention is to address the above-mentioned problems existing in the prior art and to propose a low-concentration, high-temperature, flame-retardant lithium-ion battery electrolyte that is compatible with graphite, which can cover the surface of the graphite negative electrode with a lithium fluoride-rich SEI, control the side reactions at the interface, and enable the ion battery to operate stably at a high temperature of 60°C.

[0004] The purpose of the present invention can be achieved by the following technical solutions:

[0005] A low-concentration, high-temperature, flame-retardant lithium-ion battery electrolyte compatible with graphite, the raw materials of which include an organic solvent and a lithium salt; the organic solvent includes a carbonate compound and a fluorocarbonate compound in a volume ratio of 1: (0.1-10); the thermal decomposition temperature of the lithium salt is ≥250°C.

[0006] The present invention adopts fluorinated carbonate compound solvent to improve the film-forming property, oxidation stability and combustibility of the electrolyte, and improve the comprehensive performance of the battery. The electrolyte can be decomposed at the graphite negative electrode to form a lithium fluoride-rich SEI, and the SEI film can be evenly and densely covered on the graphite surface, inhibiting the side reaction at the interface and maintaining stability during the cycle. The carbonate compound is mixed with the fluorinated carbonate compound, and the synergistic effect is used to inhibit the co-embedding of the graphite negative terminal. The electrolyte has stable properties and a high boiling point, and the high-temperature stability of the lithium-ion battery is improved. The lithium ion battery has a high thermal decomposition temperature. Salts (such as difluorooxalic acid compounds) can build a low-impedance lithium fluoride-rich SEI film on the surface of the graphite negative electrode because of the highest energy level of the highest occupied molecular orbital (HOMO). Its components include lithium oxalate, other oxalic acid species and borates. The surface film composed of decomposition products can protect the negative electrode and inhibit the decomposition of the electrolyte, forming more lithium fluoride SEI films. Because it has a higher Young's model, the SEI film is dense and stable; at the same time, more lithium fluoride / lithium carbonate interfaces are formed, which improves ionic conductivity. Thanks to the composition and structure of the SEI film, graphite / lithium batteries have good cycle stability, and lithium-ion batteries can operate stably under high temperature and high pressure.

[0007] Preferably, the fluorinated carbonate compound has the general formula shown in formula (1) and / or formula (2):

[0008]

[0009] wherein RR1 comprises one of fluoroalkyl, fluoroalkyl, fluoroalkynyl, -F, alkyl, alkyl, and alkynyl;

[0010] R2 includes one of fluoroalkyl, fluoroalkyl, fluoroalkynyl, -F, alkyl, alkyl, and alkynyl;

[0011] R3 includes one of fluoroalkyl, fluoroalkyl, fluoroalkynyl, -F, alkyl, alkyl, alkynyl, and -H;

[0012] R4 includes one of fluoroalkyl, fluoroalkyl, fluoroalkynyl, -F, alkyl, alkyl, alkynyl, and -H;

[0013] At least one of R3 and R4 includes one of a fluorine-containing alkyl group, a fluorine-containing hydrocarbon group, a fluorine-containing alkynyl group, and -F.

[0014] Preferably, the cyclic carbonate is a cyclic carbonate and / or a chain carbonate.

[0015] Cyclic carbonate and / or chain carbonate compounds are stable and have a high boiling point, which is beneficial for lithium-ion batteries to operate at high temperatures; and cyclic carbonates have a high polarity, which can make lithium salts dissolve better.

[0016] More preferably, the cyclic carbonate includes one or more of ethylene carbonate, propylene carbonate and butylene carbonate; the chain carbonate includes one or more of dimethyl carbonate, diethyl carbonate and ethyl methyl carbonate.

[0017] More preferably, the carbonate compound is propylene carbonate, and its structural formula is shown in formula (3):

[0018]

[0019] Preferably, the fluorinated carbonate compound includes one or more of fluorinated ethylene carbonate, bisfluoroethylene carbonate, methyl trifluoroethyl carbonate, di(2,2,2-trifluoroethyl) carbonate, and 2,2,2-trifluoroethyl ethyl carbonate.

[0020] More preferably, the fluorocarbonate compound is methyl trifluoroethyl carbonate, and its structural formula is shown in formula (4):

[0021]

[0022] Preferably, the volume ratio of the carbonate compound to the fluorinated carbonate compound is 1:(0.5-2).

[0023] Preferably, the organic solvent is propylene carbonate and methyl trifluoroethyl carbonate in a volume ratio of 1:(0.7-1.4).

[0024] More preferably, the organic solvent is propylene carbonate and methyl trifluoroethyl carbonate in a volume ratio of 1:1.

[0025] Preferably, the lithium salt comprises a difluorooxalate compound.

[0026] More preferably, the difluorooxalate compound includes one or more of lithium difluorooxalatoborate and lithium difluorooxalatophosphate.

[0027] More preferably, the lithium salt is lithium difluorooxalatoborate and lithium difluorooxalatophosphate in a molar ratio of 4:1.

[0028] Preferably, the concentration of the lithium salt in the low-concentration, high-temperature, flame-retardant lithium-ion battery electrolyte that is compatible with graphite is 0.01 to 1 mol / L.

[0029] Further preferably, the concentration of the lithium salt in the low-concentration, high-temperature, flame-retardant lithium-ion battery electrolyte compatible with graphite is 0.5 mol / L.

[0030] A method for preparing a low-concentration, high-temperature, flame-retardant lithium-ion battery electrolyte compatible with graphite comprises: mixing a lithium salt and an organic solvent, heating and shaking at 25 to 40° C. for 1 to 12 hours, and cooling at room temperature.

[0031] A lithium ion battery comprises a positive electrode, a negative electrode and a low-concentration, high-temperature and flame-retardant lithium ion battery electrolyte which is compatible with graphite.

[0032] Preferably, the lithium-ion battery includes one or more of NCM811 lithium-ion battery, Li / Gr battery, lithium cobalt oxide battery, and lithium iron phosphate battery.

[0033] Preferably, the lithium-ion battery has a 100-cycle capacity retention rate of >83% at 60° C. and a rate of 1C, and a self-extinguishing time of <5 s / g.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] 1. The organic solvent in the low-concentration, high-temperature, flame-retardant lithium-ion battery electrolyte compatible with graphite of the present invention includes a compound of a carbonate compound and a fluorocarbonate compound. The carbonate compound and the fluorocarbonate compound are fused together to inhibit the co-embedding of the graphite negative terminal, have stable properties and a high boiling point, and improve the high-temperature stability of the lithium-ion battery;

[0036] 2. The fluorinated carbonate compound solvent in the low-concentration, high-temperature, flame-retardant lithium-ion battery electrolyte compatible with graphite of the present invention can improve the film-forming property, oxidation stability and flammability of the electrolyte and can improve the overall performance of the battery. It can decompose at the graphite negative electrode to form a lithium fluoride-rich SEI, and this SEI film can be evenly and densely covered on the graphite surface, inhibiting side reactions at the interface and maintaining stability during the cycle;

[0037] 3. The low-concentration, high-temperature, flame-retardant lithium-ion battery electrolyte compatible with graphite of the present invention adopts a high-temperature resistant lithium salt, which has a higher thermal decomposition temperature than traditional lithium salts, which means that even at a higher operating temperature, the lithium salt can maintain relatively stable chemical properties and is not prone to thermal decomposition reactions, thereby effectively reducing side reactions caused by high temperatures and ensuring the performance of the electrolyte under high temperature conditions, so that the lithium-ion battery assembled based on the low-concentration, high-temperature, flame-retardant lithium-ion battery electrolyte compatible with graphite can operate stably at high temperatures;

[0038] 4. The low-concentration, high-temperature, flame-retardant lithium-ion battery electrolyte compatible with graphite of the present invention adopts a low-concentration lithium salt solvent ratio, which effectively reduces the amount of lithium salt used and saves costs. In addition, due to its lower viscosity, it can improve the penetration and transmission efficiency of the electrolyte inside the electrode material and the battery structure, ensuring that lithium ions can achieve rapid and uniform migration on the electrode surface, thereby improving the charge and discharge efficiency and rate performance of the battery, that is, it has good electrochemical kinetic performance;

[0039] 5. The anions of the lithium salt used in the present invention can enhance the interaction between lithium ions and other anions and enhance the complexation; and the synergistic effect of the fluorocarbonate compound solvent and the lithium salt can greatly improve the solvation structure of the electrolyte and can be more compatible with graphite;

[0040] 6. The lithium-ion battery based on the low-concentration, high-temperature, flame-retardant lithium-ion battery electrolyte compatible with graphite of the present invention can achieve stable operation at a high temperature of 60°C, so that the lithium-ion battery can maintain a stable state of the electrolyte in a high-temperature environment, avoiding problems such as electrolyte decomposition, intensified side reactions, and decreased conductivity caused by high temperature, thereby expanding the application in electric vehicles, energy storage systems, and other electronic devices operating under high-temperature environmental conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 0.1C rate charge and discharge cycle curves of Li / Gr batteries assembled with the electrolyte of Example 1 of the present invention (denoted as PF41), the electrolyte of Comparative Example 1 (denoted as P41), the electrolyte of Comparative Example 2 (denoted as PF5), and the electrolyte of Comparative Example 3 (denoted as P5).

[0042] Figure 2 Cyclic voltammetry test curves of Li / Gr batteries assembled with the electrolyte of Example 1 of the present invention (denoted as PF41), the electrolyte of Comparative Example 1 (denoted as P41), the electrolyte of Comparative Example 2 (denoted as PF5), and the electrolyte of Comparative Example 3 (denoted as P5).

[0043] Figure 3 The graphite after the electrolyte of Example 1 (denoted as PF41) is circulated with the electrolyte of Comparative Example 1 (denoted as P41), the electrolyte of Comparative Example 2 (denoted as PF5), and the electrolyte of Comparative Example 3 (denoted as P5) are assembled into Li / Gr battery charge and discharge curves. DETAILED DESCRIPTION

[0044] The following are specific embodiments of the present invention, which further describe the technical solutions of the present invention, but the present invention is not limited to these embodiments.

[0045] Unless otherwise specified, the materials used in the present invention are conventional commercial products, and the methods used are conventional technical means.

[0046] Example 1

[0047] Preparation method of low-concentration high-temperature flame-retardant lithium-ion electrolyte compatible with graphite:

[0048] After mixing propylene carbonate and methyl trifluoroethyl carbonate in a volume ratio of 1:1, lithium difluorooxalatoborate and lithium difluorobisoxalatophosphate in a molar ratio of 4:1 were added, and the concentration of lithium salt in the electrolyte was 0.5 mol / L; then, the mixture was heated and shaken at 30°C for 6 hours and then cooled at room temperature to obtain a low-concentration, high-temperature flame-retardant lithium ion electrolyte (denoted as PF41) compatible with graphite.

[0049] Preparation method of NCM811 lithium-ion battery:

[0050] The positive electrode active material NCM811, the binder polyvinylidene fluoride, and the conductive agent Super-P are mixed in a weight ratio of 8:1:1, N-methylpyrrolidone is added, and the mixture is stirred evenly to form a positive electrode slurry; the positive electrode slurry is evenly coated on an aluminum foil with a thickness of 25 μm; the aluminum foil is dried at room temperature and then transferred to a 110°C oven for drying for 8 hours, and then rolled and cut to obtain an NCM811 positive electrode sheet;

[0051] The negative electrode active material graphite, thickener sodium carboxymethyl cellulose, binder styrene-butadiene rubber, and conductive agent Super-P are mixed in a weight ratio of 90:3:3:4, deionized water is added, and stirred evenly to form a negative electrode slurry; the negative electrode slurry is evenly coated on a copper foil with a thickness of 10 μm; the copper foil is dried at room temperature and then transferred to an oven at 80°C for drying for 8 hours, and then rolled and cut to obtain a graphite negative electrode sheet;

[0052] The positive electrode shell, pole piece, diaphragm, graphite pole piece, gasket, spring piece and negative electrode shell are stacked in order, the low-concentration high-temperature flame-retardant lithium-ion electrolyte compatible with graphite prepared above is injected, and then packaged at a pressure of 50MPa, and then kept at a constant temperature of 25°C for more than 12 hours to obtain an NCM811 lithium-ion battery.

[0053] The NCM811 lithium-ion battery was subjected to a 60°C high temperature cycle performance test: before the test, the battery was placed in a 60°C environment and left to stand for 20 minutes. When the battery body temperature reached 60°C, a charge and discharge test was performed at a rate of 1C, and a flame retardant test was performed on the electrolyte. The results are shown in Table 1.

[0054] Preparation method of Li / Gr battery:

[0055] The active material graphite, the thickener sodium carboxymethyl cellulose, the binder styrene-butadiene rubber, and the conductive agent Super-P are mixed in a weight ratio of 90:3:3:4, deionized water is added, and the mixture is stirred evenly to form a negative electrode slurry; the negative electrode slurry is evenly coated on a copper foil with a thickness of 10 μm; the copper foil is dried at room temperature and then transferred to an oven at 80°C for drying for 8 hours, and then rolled and cut to obtain a graphite negative electrode sheet;

[0056] The positive electrode shell, graphite pole piece, diaphragm, lithium sheet, gasket, spring piece and negative electrode shell are stacked in order, the low-concentration high-temperature flame-retardant lithium ion electrolyte compatible with graphite prepared above is injected, and then packaged at a pressure of 50MPa, and then kept at a constant temperature of 25°C for more than 12 hours to obtain a Li / Gr battery.

[0057] The above-mentioned Li / Gr battery was subjected to a 25°C room temperature cycle performance test: before the test, the battery was placed in an environment of 25°C for 5 minutes, and then a charge and discharge test was performed at a rate of 0.1C.

[0058] The prepared graphite-compatible low-concentration, high-temperature, flame-retardant lithium-ion electrolyte Li / Gr battery was subjected to a cyclic voltammetry test at 25°C.

[0059] Figure 1 It is the charge and discharge curve of Li / Gr battery at 0.1C; Figure 2 This is the cyclic voltammetry test diagram of Li / Gr battery.

[0060] Example 2

[0061] Preparation method of low-concentration high-temperature flame-retardant lithium-ion electrolyte compatible with graphite:

[0062] After mixing propylene carbonate and fluoroethylene carbonate in a volume ratio of 1:1, lithium difluorooxalatoborate and lithium difluorobisoxalatophosphate in a molar ratio of 4:1 are added, and the concentration of lithium salt in the electrolyte is 0.5 mol / L; then, the mixture is heated and shaken at 30°C for 6 hours and then cooled at room temperature to obtain a low-concentration, high-temperature, flame-retardant lithium-ion electrolyte compatible with graphite.

[0063] The low-concentration, high-temperature, flame-retardant lithium-ion electrolyte in this embodiment is assembled according to the preparation method of the NCM811 lithium-ion battery in Example 1. The performance results of the NCM811 lithium-ion battery are shown in Table 1.

[0064] Example 3

[0065] Preparation method of low-concentration high-temperature flame-retardant lithium-ion electrolyte compatible with graphite:

[0066] After mixing propylene carbonate and ethylene difluorocarbonate in a volume ratio of 1:1, lithium difluorooxalatoborate and lithium difluorobisoxalatophosphate were added in a molar ratio of 4:1, and the concentration of lithium salt in the electrolyte was 0.5 mol / L; then, the mixture was heated and shaken at 30°C for 6 hours and then cooled at room temperature to obtain a low-concentration, high-temperature, flame-retardant lithium-ion electrolyte compatible with graphite.

[0067] The low-concentration, high-temperature, flame-retardant lithium-ion electrolyte in this embodiment is assembled according to the preparation method of the NCM811 lithium-ion battery in Example 1. The performance results of the NCM811 lithium-ion battery are shown in Table 1.

[0068] Example 4

[0069] Preparation method of low-concentration, high-temperature, flame-retardant lithium-ion electrolyte compatible with graphite:

[0070] After mixing propylene carbonate and methyl trifluoroethyl carbonate in a volume ratio of 1:1, lithium difluorooxalatoborate and lithium difluorodioxalatophosphate in a molar ratio of 1:1 were added, and the concentration of lithium salt in the electrolyte was 0.5 mol / L; then, the mixture was heated and shaken at 30°C for 6 hours and then cooled at room temperature to obtain a low-concentration, high-temperature, flame-retardant lithium-ion electrolyte compatible with graphite.

[0071] The low-concentration, high-temperature, flame-retardant lithium-ion electrolyte in this embodiment is assembled according to the preparation method of the NCM811 lithium-ion battery in Example 1. The performance results of the NCM811 lithium-ion battery are shown in Table 1.

[0072] Example 5

[0073] Preparation method of low-concentration, high-temperature, flame-retardant lithium-ion electrolyte compatible with graphite:

[0074] After mixing propylene carbonate and methyl trifluoroethyl carbonate in a volume ratio of 1:1, lithium difluorooxalatoborate and lithium difluorodioxalatophosphate in a molar ratio of 3:1 are added, and the concentration of lithium salt in the electrolyte is 0.5 mol / L; then, the mixture is heated and shaken at 30°C for 6 hours and then cooled at room temperature to obtain a low-concentration, high-temperature, flame-retardant lithium-ion electrolyte compatible with graphite.

[0075] The low-concentration, high-temperature, flame-retardant lithium-ion electrolyte in this embodiment is assembled according to the preparation method of the NCM811 lithium-ion battery in Example 1. The performance results of the NCM811 lithium-ion battery are shown in Table 1.

[0076] Comparative Example 1

[0077] Preparation method of low-concentration, high-temperature, flame-retardant lithium-ion electrolyte compatible with graphite:

[0078] Lithium difluorooxalatoborate and lithium difluorobisoxalatophosphate were added to propylene carbonate in a molar ratio of 4:1, and the concentration of lithium salt in the electrolyte was 0.5 mol / L; then the mixture was heated and shaken at 30°C for 6 hours and then cooled at room temperature to obtain a low-concentration, high-temperature, flame-retardant lithium ion electrolyte (denoted as P41) that is compatible with graphite.

[0079] The low-concentration, high-temperature, flame-retardant lithium-ion electrolyte in this comparative example was assembled according to the preparation method of the NCM811 lithium-ion battery in Example 1. The performance results of the NCM811 lithium-ion battery are shown in Table 1.

[0080] The Li / Gr battery assembled with PF41 electrolyte in Example 1 was disassembled after the first cycle charge and discharge test, the graphite negative electrode was taken out, and the Li / Gr battery was reassembled with P41 electrolyte for charge and discharge cycles.

[0081] Figure 3 (a) Assembly and recycling diagram of Li / Gr graphite battery with P41 electrolyte after cycling with PF41 electrolyte.

[0082] Comparative Example 2

[0083] Preparation method of low-concentration, high-temperature, flame-retardant lithium-ion electrolyte compatible with graphite:

[0084] After mixing propylene carbonate and methyl trifluoroethyl carbonate in a volume ratio of 1:1, lithium difluorooxalatoborate is added, and the concentration of lithium salt in the electrolyte is 0.5 mol / L; then, the mixture is heated and shaken at 30°C for 6 hours and then cooled at room temperature to obtain a low-concentration, high-temperature, flame-retardant lithium ion electrolyte (denoted as PF5) that is compatible with graphite.

[0085] The low-concentration, high-temperature, flame-retardant lithium-ion electrolyte in this comparative example was assembled according to the preparation method of the NCM811 lithium-ion battery in Example 1. The performance results of the NCM811 lithium-ion battery are shown in Table 1.

[0086] The Li / Gr battery assembled with PF41 electrolyte in Example 1 was disassembled after the first cycle charge and discharge test, the graphite negative electrode was taken out, and the Li / Gr battery was reassembled with PF5 electrolyte for charge and discharge cycles.

[0087] Figure 3 (b) A diagram of the Li / Gr graphite battery assembled and recycled using PF5 electrolyte after cycling with PF41 electrolyte.

[0088] Comparative Example 3

[0089] Preparation method of low-concentration, high-temperature, flame-retardant lithium-ion electrolyte compatible with graphite:

[0090] Lithium difluorooxalatoborate was added to propylene carbonate, and the concentration of lithium salt in the electrolyte was 0.5 mol / L; then, the mixture was heated and shaken at 30°C for 6 hours and then cooled at room temperature to obtain a low-concentration, high-temperature, flame-retardant lithium-ion electrolyte (denoted as P5) that was compatible with graphite.

[0091] The low-concentration, high-temperature, flame-retardant lithium-ion electrolyte in this comparative example was assembled according to the preparation method of the NCM811 lithium-ion battery in Example 1. The performance results of the NCM811 lithium-ion battery are shown in Table 1.

[0092] The Li / Gr battery assembled with PF41 electrolyte in Example 1 was disassembled after the first cycle charge and discharge test, the graphite negative electrode was taken out, and the Li / Gr battery was reassembled with P5 electrolyte for charge and discharge cycles.

[0093] Figure 3 (c) is a diagram of the Li / Gr graphite battery assembled and recycled using P5 electrolyte after cycling with PF41 electrolyte.

[0094] Comparative Example 4

[0095] Preparation method of low-concentration, high-temperature, flame-retardant lithium-ion electrolyte compatible with graphite:

[0096] Lithium difluorooxalatoborate is added to propylene carbonate, and the concentration of lithium salt in the electrolyte is 1 mol / L; then, the electrolyte is heated and shaken at 30°C for 6 hours and then cooled at room temperature to obtain a low-concentration, high-temperature, flame-retardant lithium-ion electrolyte that is compatible with graphite.

[0097] The low-concentration, high-temperature, flame-retardant lithium-ion electrolyte in this comparative example was assembled according to the preparation method of the NCM811 lithium-ion battery in Example 1. The performance results of the NCM811 lithium-ion battery are shown in Table 1.

[0098] Table 1. Performance test results of NCM811 lithium-ion battery at 60°C

[0099]

[0100] According to Table 1, the combination of propylene carbonate and methyl trifluoroethyl carbonate in a volume ratio of 1:1 and lithium difluorooxalatoborate and lithium difluorobisoxalatophosphate in a molar ratio of 4:1 in Example 1 of the present invention, the low-concentration, high-temperature flame-retardant lithium-ion battery electrolyte compatible with graphite is prepared, which is applied to lithium-ion batteries and can achieve stable operation at a high temperature of 60°C.

[0101] The use of different fluorocarbonate compounds in Examples 2 and 3 has a certain influence on the performance of lithium-ion batteries. Fluorinated carbonate compounds reduce the hydrogen content and flammability of solvent molecules, and cyclic fluorocarbonates have a higher viscosity.

[0102] Adjusting the ratio of lithium difluorooxalatoborate to lithium difluorooxalatophosphate in Examples 4 and 5 has a certain influence on the performance of lithium ion batteries. Lithium difluorooxalatophosphate has the ability to form positive and negative electrodes, can inhibit the decomposition of the electrolyte, form a SEI film containing more LiF, and can react preferentially with the solvent.

[0103] In Comparative Example 1, the organic solvent is only propylene carbonate, and in Comparative Example 2, the lithium salt is only lithium difluorooxalatoborate, both of which lead to decreased cycle performance and flame retardancy of the lithium ion battery; in Comparative Example 3, the organic solvent is only propylene carbonate, and the lithium salt is only lithium difluorooxalatoborate, which leads to further decreased cycle performance and flame retardancy of the lithium ion battery; it shows that lithium difluorobisoxalate phosphate and methyl trifluoroethyl carbonate can inhibit the co-embedding of propylene carbonate to a certain extent, and the synergistic effect of lithium difluorobisoxalate phosphate and methyl trifluoroethyl carbonate can achieve stable cycle and flame retardancy of propylene carbonate-based electrolyte.

[0104] from Figure 1 It can be seen that the PF41 electrolyte can be charged and discharged normally, but the P5, P41 and PF5 electrolytes will be co-embedded with graphite.

[0105] from Figure 2 It can be seen that the Li / Gr battery assembled with PF41 electrolyte has a reversible oxidation peak at 0.3V, and there is no reversible oxidation peak after P5 electrolyte, P41 electrolyte and PF5 electrolyte. The three electrolytes have undergone propylene carbonate co-intercalation reaction before reaching 0.3V. And the co-intercalation potential of P5 electrolyte is larger than that of P41 electrolyte and PF5 electrolyte. This shows that P5 electrolyte is more prone to propylene carbonate co-intercalation, and the addition of lithium difluorobisoxalate phosphate and methyl trifluoroethyl carbonate can inhibit the co-intercalation of propylene carbonate to a certain extent, and the synergistic effect of lithium difluorobisoxalate phosphate and methyl trifluoroethyl carbonate can achieve stable circulation of propylene carbonate-based electrolytes.

[0106] from Figure 3 (a~c) It can be seen that the reassembled battery cannot be charged and discharged normally; and the co-embedding potential of the reassembled battery is the same as the co-embedding potential of the battery directly assembled with the original graphite electrode; Generally speaking, the SEI layer can be formed in the first cycle, that is, the graphite after the first cycle of PF41 has formed a stable SEI film, and the reassembly still cannot circulate normally, so the electrolyte solvation structure is also a factor that determines the co-embedding with graphite.

[0107] In summary, the lithium-ion battery based on the graphite-compatible low-concentration high-temperature flame-retardant lithium-ion battery electrolyte of the present invention can achieve stable operation at a high temperature of 60°C, so that the lithium-ion battery can maintain a stable state of the electrolyte in a high temperature environment.

[0108] The specific embodiments described herein are merely examples of the spirit of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in similar ways, but they will not deviate from the spirit of the present invention or exceed the scope defined by the appended claims.

Claims

1. A low-concentration, high-temperature, flame-retardant lithium-ion battery electrolyte compatible with graphite, characterized in that: The raw materials include organic solvent and lithium salt; the organic solvent includes carbonate compound and fluorocarbonate compound in a volume ratio of 1: (0.1-10); the thermal decomposition temperature of the lithium salt is ≥250°C.

2. The low-concentration, high-temperature, flame-retardant lithium-ion battery electrolyte compatible with graphite according to claim 1, characterized in that: The fluorinated carbonate compound has the general formula shown in formula (1) and / or formula (2): Wherein R1 includes one of fluoroalkyl, fluoroalkyl, fluoroalkynyl, -F, alkyl, alkyl, and alkynyl; R2 includes one of fluoroalkyl, fluoroalkyl, fluoroalkynyl, -F, alkyl, alkyl, and alkynyl; R3 includes one of fluoroalkyl, fluoroalkyl, fluoroalkynyl, -F, alkyl, alkyl, alkynyl, and -H; R4 includes one of fluoroalkyl, fluoroalkyl, fluoroalkynyl, -F, alkyl, alkyl, alkynyl, and -H; At least one of R3 and R4 includes one of a fluorine-containing alkyl group, a fluorine-containing hydrocarbon group, a fluorine-containing alkynyl group, and -F.

3. The low-concentration, high-temperature, flame-retardant lithium-ion battery electrolyte compatible with graphite according to claim 1, characterized in that: The cyclic carbonate is a cyclic carbonate and / or a chain carbonate; the cyclic carbonate includes one or more of ethylene carbonate, propylene carbonate and butylene carbonate; the chain carbonate includes one or more of dimethyl carbonate, diethyl carbonate and ethyl methyl carbonate.

4. The graphite-compatible low-concentration, high-temperature, flame-retardant lithium-ion battery electrolyte according to claim 1, characterized in that: The lithium salt includes difluorooxalic acid compounds; the difluorooxalic acid compounds include one or more of difluorooxalato lithium borate and difluorooxalato lithium phosphate.

5. The low-concentration, high-temperature, flame-retardant lithium-ion battery electrolyte compatible with graphite according to claim 1, characterized in that: The concentration of the lithium salt in the low-concentration, high-temperature, flame-retardant lithium-ion battery electrolyte that is compatible with graphite is 0.01-1 mol / L.

6. The graphite-compatible low-concentration, high-temperature, flame-retardant lithium-ion battery electrolyte according to claim 1, characterized in that: The volume ratio of the carbonate compound to the fluorinated carbonate compound is 1:(0.5-2).

7. The graphite-compatible low-concentration, high-temperature, flame-retardant lithium-ion battery electrolyte according to claim 1, characterized in that: The organic solvent is propylene carbonate and methyl trifluoroethyl carbonate in a volume ratio of 1:1; the lithium salt is lithium difluorooxalatoborate and lithium difluorobisoxalatophosphate in a molar ratio of 4:

1.

8. A method for preparing a low-concentration, high-temperature, flame-retardant lithium-ion battery electrolyte compatible with graphite as claimed in claim 1, characterized in that: The preparation method comprises: mixing lithium salt and organic solvent, heating and shaking at 25-40° C. for 1-12 hours, and cooling at room temperature.

9. A lithium ion battery, characterized in that: The lithium-ion battery comprises a positive electrode, a negative electrode and the low-concentration, high-temperature, flame-retardant lithium-ion battery electrolyte compatible with graphite as claimed in claim 1.

10. The lithium ion battery according to claim 9, characterized in that: The lithium ion battery has a 100-cycle capacity retention rate of more than 83% at 60° C. and a rate of 1C, and a self-extinguishing time of less than 5 s / g.